Research handbook on knowledge transfer and international business - Khan, Zaheer; Nair, Smitha R.; Lew, Yong Kyu (Research handbooks in business and management series, 2022)
"This comprehensive and engaging Research Handbook provides a full examination of the modes and mechanisms of international knowledge transfer. Furthermore, it also provides in-depth insights into international knowledge transfer related challenges faced by multinational enterprises (MNEs). Chapters written by well-respected contributors provide extensive insights into the economic, technological, social, cultural and organizational aspects of knowledge transfer in international business and management. They also highlight the contextual influences imposed by the industrial sectors and countries that MNEs are associated with. Organised into three thematic parts, this Research Handbook provides interesting and important directions for future research within each chapter giving readers an opportunity to pursue these in greater depth. This timely Research Handbook will be an invaluable resource for scholars and researchers of international business and knowledge management. The practical case studies will provide a greater understanding of the topic and its challenges for managers of MNEs"--